Congenital acral verrucous hemangioma: A rare entity - Kamal Nain Rattan; Rajnish Kalra; Renuka Verma; Sunita Singh; Monika Gupta; Megha Ralli (Wolters Kluwer Medknow Publications, 2019)
Verrucous hemangioma is an uncommon capillary or cavernous hemangioma with reactive epidermal changes of hyperkeratosis, acanthosis, and papillomatosis. Lesions are mostly seen at birth or appear during childhood. These growths are usually located on the lower extremities, and involvement is generally unilateral. Diagnosis of this unusual presentation can only be confirmed following histopathology. Surgical excision resulted in a satisfactory functional and cosmetic outcome.